Integrating Hydrological Modeling and Pavement Evaluation to Analyze the Impact of Drainage Performance on Road Infrastructure - Farida, Ida; Habil Khadafi , Muhammad; Wijaya, Alan Wijaya (UIR PRESS, 2025)
The drainage channel along Gatot Subroto Road in Karangpawitan District, Garut Regency, extends about 1,580 meters in an open rectangular form with varying cross-sectional dimensions. Reports from the Public Works and Spatial Planning Agency (UPT PUPR) indicate frequent overflow and partial malfunction, mainly due to additional inflow from residential drainage and undersized sections. These conditions contribute to recurrent flooding, disruption of community activities, and accelerated pavement deterioration. This study aims to quantify design flood discharge, assess the hydraulic capacity of the existing system, evaluate pavement condition influenced by runoff, and recommend redesigned channel dimensions using hydrological hydraulic analysis with the SWMM model. A quantitative approach was applied, integrating rainfall frequency analysis, hydraulic evaluation, and Pavement Condition Index (PCI) surveys. The results show that under a 2 year return period, most segments performed adequately, whereas at 5 and 10 year periods several sections exceeded their capacity. PCI surveys yielded an average value of 58.66, categorized as “Fair,” with critical segments falling into failure due to uncontrolled runoff. After redesign, channel performance improved substantially, with Max/Full Flow ratios consistently below 1 across all segments and return periods. The findings confirm a direct relationship between drainage performance and pavement deterioration. Integrating SWMM based modeling with PCI analysis provides a robust framework for diagnosing deficiencies and formulating technical recommendations. These results are consistent with previous studies, emphasizing that drainage adequacy and pavement condition must be addressed together to improve resilience and extend the service life of urban road infrastructure.